Special paperAcute coronary syndrome as a result of left main coronary artery stenosis after aortic valve replacement. A report of three cases - Araszkiewicz, Aleksander; Lesiak, Maciej; Urbanowicz, Tomasz; Jankiewicz, Stanisław; Grajek, Stefan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Acute coronary syndrome (ACS) as a result of iatrogenic coronary ostial stenosis (ICOS) is a rare but potentially life-threatening complication of aortic valve replacement (AVR). We present three cases of patients with ACS shortly after AVR, in whom ICOS were revealed. They refused an operation and thus they were treated with percutaneous coronary intervention. The potential pathomechanisms of ICOS and treatment options are discussed.